The Development of Problem Based Learning Google Sites-Assisted Digital Teaching Materials to Improve Students' Mathematical Critical Thinking Ability - Nurdin, Irfan Taufik; Putra, Harry Dwi; Hidayat, Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematics learning has a very important role in the educational environment. That one of the competency standards for graduates of the mathematics subject for elementary to secondary education units is so that students have the skills to think and act creatively, productively, critically, independently, collaboratively and communicatively. Based on these graduate competencies, it is clear that one of the thinking skills that students must have is critical thinking. The purpose of this study was to look at students' mathematical critical thinking skills whose learning used the Problem Based Learning (PBL) model through digital teaching materials . This study uses the Research and Development (R&D) method with the ADDIE development model which consists of 5 (five) stages, namely: Analysis , Design , and Development , Implementation and Evaluation on MTs . The research subjects were 20 students of class VI I I MTS (twenty) students. Data collection techniques used were walkthroughs, questionnaires, questionnaires, interviews, and tests. Research data were analyzed quantitatively and qualitatively. The results of data analysis are known that this research produces students' critical thinking mathematics for digital teaching materials through a problem-based learning model in a flat sided geometric content that is valid and has potential effects. In this case, mathematics teaching materials that are presented digitally with a problem-based learning approach model are obtained from the results of one-to-one revisions , expert revision, small group trials and large group trials . Furthermore, the prototype of digital teaching materials is in the form of Google sites This is in addition to being effective, efficient, valid and practical, it also has a potential effect to improve students' critical thinking skills in mathematics.